Operation Pied Piper: a geographical reappraisal of the impact of wartime evacuation on scarlet fever and diphtheria rates in England and Wales, 1939–1945 - Smallman-Raynor, Matthew; Cliff, Andrew (Cambridge University Press, 2015)
This paper examines the geographical impact of the British Government’s wartime evacuation scheme on notified rates of two common acute childhood diseases (scarlet fever and diphtheria) in the 1470 local government districts of England and Wales, 1939–1945. Drawing on the notifications of communicable diseases collated by the General Register Office (GRO), we establish pre-war (baseline) disease rates for the 1470 districts. For the war years, techniques of binary logistic regression analysis are used to assess the associations between (a) above-baseline (‘raised’) disease rates in evacuation, neutral and reception districts and (b) the major phases of the evacuation scheme. The analysis demonstrates that the evacuation was temporally associated with distinct national and regional effects on notified levels of disease activity. These effects were most pronounced in the early years of the dispersal (1939–1941) and corresponded with initial levels of evacuation-related population change at the regional and district scales.